LIQUID CHROMATOGRAPHY–MASS SPECTROMETRY/MASS SPECTROMETRY METHOD FOR THE DETERMINATION OF LAPATINIB IN RAT PLASMA: APPLICATION TO PHARMACOKINETIC STUDIES IN WISTAR RATS - PALNATI, NARMADA; KOTAPATI, NALINI; VAIDYANATHAN, GOPAL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to develop and validate a simple, accurate, and sensitive liquid chromatography–mass spectrometry (LC–MS)/MS method for the determination of lapatinib a dual tyrosine kinase inhibitor in rat plasma using gefitinib as internal standard. Methods: An Inertsil ODS column (50 mm×4.6 mm×5 μm) was used for separation with isocratic elution of 10 mM ammonium formate-acetonitrile (5:95 v/v). Analyte and internal standard were extracted from 50 μl of plasma using tertiary butyl methyl ether followed by subsequent reconstitution in a mixture of water-acetonitrile. Results: The extraction recoveries were 95% and 98% for lapatinib and gefitinib, respectively. The lower limit of quantification was 5 ng/ml with a precision of 6.2% and accuracy of 108%. The response was found to be linear over the range of 5–1000 ng/ml with a correlation coefficient of 0.999. The intraday and interday precision expressed as relative standard deviation was <15%. Conclusion: This validated method was applied to the pharmacokinetic study in Wistar rats. The proposed bioanalytical LC–MS/MS method for lapatinib is a simple, sensitive, and accurate to quantify the concentrations in rat plasma.